Pembatalan Akta Pengikatan Jual Beli Yang Dibuat Di Hadapan Notaris Karena Wanprestasi - Fitriasih Fitriasih (Officium Notarium, 2021)
The deed of sale and purchase agreement number 53 dated 27 November 2013 drawn up before a notary is a valid agreement between PT Bantul Kota Mandiri and PT Rumah Cerdas. As a result of the defendant’s actions of not paying off the payment or default and having been reprimanded by the plaintiff to make the payment, the plaintiff filed a lawsuit for cancellation of the agreement at the Bantul District Court. The formulation of the problem in this study is first, what is the basis for the consideration of the Bantul District Court judge in canceling the sale and purchase binding deed made before a notary due to default? Second, what are the legal consequences of canceling the sale and purchase binding deed made before a notary because of a default? This type of research is normative juridical using two approaches, namely the statutory and the case approaches. There are 2 (two) conclusions, first, the decision to cancel the sale and purchase binding deed between PT Bantul Kota Mandiri and PT Rumah Cerdas is correct from a philosophical, juridical and sociological aspect and from a justice perspective it has fulfilled legal justice, social justice and moral justice. Second, due to the decision to cancel the sale and purchase binding deed, the deed has no legal force, cannot be used as evidence and the parties’ rights are returned as before the agreementKey Word: Deed cancellation, judge decision, justiceAbstrakAkta pengikatan jual beli nomor 53 tertanggal 27 November 2013 yang dibuat dihadapan notaris merupakan perjanjian yang sah antara PT Bantul Kota Mandiri dan PT Rumah Cerdas. Akibat perbuatan tergugat yang tidak melunasi pembayaran atau wanprestasi dan telah ditegur oleh penggugat untuk melakukan pembayaran sehingga penggugat mengajukan gugatan pembatalan perjanjian di Pengadilan Negeri Bantul. Adapun rumusan masalah dalam penelitian ini adalah, pertama, apakah dasar pertimbangan hakim Pengadilan Negeri Bantul dalam pembatalan akta pengikatan jual beli yang dibuat di hadapan notaris karena wanprestasi sudah tepat ? Kedua, bagaimanakah akibat hukum pembatalan akta pengikatan jual beli yang dibuat di hadapan notaris karena wanprestasi? Jenis penelitian ini adalah yuridis normatif dengan menggunakan dua pendekatan yaitu pendekatan perundang-undangan dan pendekatan kasus. Terdapat 2 (dua) kesimpulan bahwa, pertama, putusan pembatalan akta pengikatan jual beli antara PT Bantul Kota Mandiri dan PT Rumah Cerdas sudah tepat dilihat dari aspek filosofis, yuridis dan sosiologis serta dari sisi keadilan telah memenuhi legal justice, social justice dan moral justice. Kedua, akibat putusan pembatalan akta pengikatan jual beli maka akta tersebut tidak memiliki kekuatan hukum, tidak dapat dijadikan alat bukti dan para pihak hak-haknya dikembalikan seperti sebelum ada perjanjianKata Kunci: Keadilan, Pembatalan Akta, Putusan Hakim